Acoustical relaxation in heterocyclic liquids - LINDE, Bogumił (Archives of Acoustics, 1982)
Measurements of ultrasonic velocity and ultrasonic absorption coefficient have been carried out for several organic liquids in the frequency range from 10 to 1300 MHz at 293 K temperature.The ultrasonic measurements and the infrared spectra of the liquids have been used for determination of vibrational degrees of freedom which take part in acoustical relaxation process.